Design and Analysis of Smart Laptop Table Production with an Ergonomic Approach and Minimalist Design - Oki Pratama; Trifenaus Prabu Hidayat (Metris: Jurnal Sains dan Teknologi, 2025)
This study focuses on the design and development of a smart ergonomic laptop table with a modern and minimalist aesthetic to enhance user comfort and prevent musculoskeletal disorders during prolonged laptop use. Using the Stanford Design Thinking methodology, the research was conducted through six stages: empathize, define, ideate, prototype, test, and assessment. Data were collected from 26 respondents through surveys and interviews to identify key user needs, including adjustable height and tilt, integrated cooling pad, power socket, and portability. The prototype, constructed from Dutch teak wood and a hollow iron frame, was analyzed through stress, displacement, and strain simulations to ensure structural reliability and durability. The results demonstrated that the final design effectively supports ergonomic posture, reduces discomfort in the neck, back, shoulders, and wrists, and prevents repetitive strain injuries. Additionally, the product combines functional efficiency with an appealing minimalist appearance suitable for modern workspaces. The proposed design not only improves user well-being and productivity but also contributes to sustainable and space-efficient furniture innovation.